CONCENTRATION AND CONTENT OF MACRONUTRIENT IN THE Mimosa scabrella BENTHAM BIOMASS, AT DIFFERENT SITE, AGE AND DIAMETER CLASSES - TÉO, Saulo Jorge; MACHADO, Sebastião do Amaral; REISSMANN, Carlos Bruno; FIGUEIREDO FILHO, Afonso (Scientia Agraria, 2010)
The aims of this work were to quantify and to evaluate macronutrient concentration and content of the Mimosa scabrella Bentham above-ground biomass under different site, age and diameter classes. Twenty five trees were sampled in several stands of the Curitiba metropolitan region, Paraná State, Brazil. In the field, the trees were measured and separated in leaves, twigs, branches, stem wood and bark. Later on, a fraction of each tree component was carried to the laboratory for the determination of dry weight and macronutrient. The site, age and diameter class effects were evaluated by completely random statistic design. The results showed that, the macronutrient concentration by compartment of biomass presented the following decreasing order: leaves > stem bark > twigs > branches > stem wood. The macronutrient content in the stem wood presented the highest quantity. According to the results, the macronutrient concentrations of the Mimosa scabrella above-ground biomass didn’t show any relationship with the age and diameter classes, on the other hand, P and K leaf concentrations increased with site quality. There was no relationship between macronutrient content of the Mimosa scabrella above-ground biomass, site and age classes. Nevertheless, diameter classes presented a significant and coherent influence over macronutrient content, which increases with the diameter classes.